2016
DOI: 10.18632/oncotarget.13866
|View full text |Cite
|
Sign up to set email alerts
|

TM4SF1 promotes the self-renewal of esophageal cancer stem-like cells and is regulated by miR-141

Abstract: Cancer stem-like cells have been identified in primary human tumors and cancer cell lines. Previously we found TM4SF1 gene was highly expressed in side population (SP) cells from esophageal squamous cell carcinoma (ESCC) cell lines, but the role and underlying mechanism of TM4SF1 in ESCC remain unclear. In this study, we observed TM4SF1 was up-regulated but miR-141 was down-regulated in SP cells isolated from ESCC cell lines. TM4SF1 could stimulate the self-renewal ability and carcinogenicity of esophageal can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…Xue et al (34) demonstrated that matrix metallopeptidase (MMP)-2, MMP-9 and VEGF are the downstream proteins of TM4SF1, and TM4SF1 overexpression in turn upregulated MMP-2, MMP-9 and VEGF expression. VEGF is known to be a strong angiogenic factor, and the binding of VEGF and its receptors may stimulate endothelial cell division, proliferation and migration, promote physiological and pathological neovascularization, increase microvascular permeability and promote embryonic hematopoiesis (35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…Xue et al (34) demonstrated that matrix metallopeptidase (MMP)-2, MMP-9 and VEGF are the downstream proteins of TM4SF1, and TM4SF1 overexpression in turn upregulated MMP-2, MMP-9 and VEGF expression. VEGF is known to be a strong angiogenic factor, and the binding of VEGF and its receptors may stimulate endothelial cell division, proliferation and migration, promote physiological and pathological neovascularization, increase microvascular permeability and promote embryonic hematopoiesis (35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…Transmembrane 4 L6 family proteins have been reported to be closely related to cancer malignancy [ 38 ]. TM4SF1 is known to promote the self-renewal of esophageal cancer stem-like cells, which is regulated by miR-141; therefore, it was defined as a prognostic marker of squamous carcinomas [ 39 ]. TM4SF5 is involved in metastasis via direct activation of FAK, promoting EMT and gefitinib-resistance of cancer cells [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using immunohistochemistry assay we found a decreased expression of SOX2 in Lenti-sh-DNMT1 or 5-aza-dC treated tumor xenografts (Figure 6C ). MiR-200 family (including miR-200A, miR-200B and miR-141) and miR-203 were reported as key regulators to suppress “stemness” in many kinds of stem cells [ 22 24 ]. So we detected the expression of these miRNAs by real-time PCR analysis.…”
Section: Resultsmentioning
confidence: 99%